COMMUNICATIVE AND PRAGMATIC PARAMETERS OF THE BLOG AS A GENRE OF PERSONAL INTERNET COMMUNICATION (BASED ON TEXTS BY LYUDMILA LINNYK ON THE WEBSITE “GALICIAN CORRESPONDENT”) - Nataliia Ya. Ivanyshyn (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article reveals the communicative and pragmatic parameters of the blog as a genre of personal Internet communication. On the material of the blog by Lyudmila Linnyk on the website «Galitsky Correspondent» it is proved that language means of different levels can participate in the process of text and character formation. They can acquire additional meanings in the process of unfolding the text, form an evaluative frame of the message, and facilitate the decoding of blog posts in the manner defined by the author mainstream. The purpose of the study is to reveal the communicative and pragmatic features of a blog as a specific genre of Internet communication. The following methods have been used in the work: descriptive (with its help we have collected and analyzed language means that are significant in the communication process), contextual (has allowed us to explore the environment of linguistic units and its impact on the result of communication) and the associative field method (has helped to identify associative links between in words, the implementation of a multilevel analysis of tokens). It is noted that various researchers base their understanding of a blog as a separate genre of communication in the network on its specific characteristics, but everyone agrees with the statement that a blog is a website with chronological, back-structured multimedia information presented in it, the content of which can be commented on. It has been found that the communicative and pragmatic potential of a blog as a genre of personal Internet communication is realized due to the actualization of linguistic means of different levels: pronouns and deictic structures, connotative and associative linguistic units, slang and pejorative elements, phraseological units, grafon, parcels, affix morphemes. It has been established that pronouns are used in blogs to intensify the text, dynamizing the storyline, and forming antinomies. Connotationally and associatively coloured linguistic units act as keywords that are nodes of a concatenation of the semantic structure of the text, the starting point for the development of the topic; they are emotionally evaluative components capable of semantically expanding the text, giving it new semantic dimensions, reflecting the blogger’s position and his individualized vision of certain social problems. Parcelled constructions perform attractively and meaningful reinforcing functions, actualize the blogger’s speech intentions. The use of grafon as a way of avoiding the graphic standard contributes to the actualization of the meanings of individual lexemes, providing them with new meanings. Slang and pejorative elements, like affixal morphemes, form evaluativeness (usually negative), expressiveness and euphemism. It is noted that different types of linguistic units can form the evaluative frame of the message, intensify the plotline, express the presentation of the material, establish connections between implications in the text and facilitate the identification of the associative meanings of the word